Exploring the effects of nanofillers of epoxy nanocomposite coating for sustainable corrosion protection - Siti Maznah, Kabeb; Azman, Hassan; Zurina, Mohamad; Zalilah, Sharer; Munirah, Mokhtar; Faiz, Ahmad (The Italian Association of Chemical Engineering-AIDIC, 2019)
Development of coating durability and sustainability for industry to facilitate the corrosion potential minimization attract much attention in recent year. The selection of appropriate coating material is necessities to improve corrosion protection of metal. Epoxy nanocomposite coatings filled with different amount of graphene nanoplateles (GNP) and montmorillonite (MMT) was prepared via mechanical agitation process to enhance the flame retardancy and anticorrosion performance of mild steel substrates. Salt fog test, limiting oxygen index (LOI) and water absorption result reveal that embedding a small amount of filler remarkably improved anticorrosion performance and flame retardancy of epoxy nanocomposite coatings. Present study suggests a development of nanocomposite coating with superior mechanical properties which was evaluated by adhesion tape test.